(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The article gives examples of work with the texts of professional direction during the teaching of the Ukrainian language as a foreign language in higher educational institutions of the pedagogical profile. The subjects of texts are intended for students of natural sciences, physics and mathematics and geography faculties. The author emphasizes foreign students receiving higher pedagogical education in different specialties must necessarily work with texts of professional orientation during Ukrainian language classes as foreign language. This will help foreign students to acquire many lexical units and syntactic constructions, which are necessary for studying of special disciplines (biology, chemistry, physics, astronomy, geography, etc.) and getting higher pedagogical education. First of all, this work is aimed at preparing foreign students for further perception and understanding of professional literature. It is emphasized that the methodology of teaching Ukrainian as a foreign language differs fundamentally from the methodology of teaching Ukrainian as a mother tongue. Such a difference is determined by a number of actual linguistic, linguo-didactic and psychological factors. Despite many textbooks and study guides for foreign students have been made, the question of finding methods of teaching Ukrainian as a foreign language remains relevant. Consequently, the relevance of the article is determined by the latest requirements aimed at improving the modern national education system in general and the language training of foreign students in particular.